Exploring competing experiences and expectations of the revitalized community health worker programme in Mozambique: an equity analysis - Give, Celso Soares (Hum Resour Health, 2015)
INTRODUCTION: Mozambique launched its revitalized community health programme in 2010 in response to inequitable coverage and quality of health services. The programme is focused on health promotion and disease prevention, with 20 % of community health workers’ (known in Mozambique as Agentes Polivalentes Elementares (APEs)) time spent on curative services and 80 % on activities promoting health and preventing illness. We set out to conduct a health system and equity analysis, exploring experiences and expectations of APEs, community members and healthcare workers supervising APEs. METHODS: This exploratory qualitative study captured the perspectives of a range of participants including women caring for children under 5 years (service clients), community leaders, service providers (APEs) and their supervisors. Participants in the Moamba and Manhiça districts, located in Maputo Province (Mozambique), were selected purposively. In total, 29 in-depth interviews and 9 focus group discussions were conducted in the local language and/or Portuguese. A framework approach was used for analysis, assisted by NVivo10 software. RESULTS: Our analysis revealed that health equity is viewed as linked to the quality and coverage of the APE programme. Demand and supply factors interplay to shape health equity. The availability of responsive and appropriate services led to tensions between community expectations for curative services (and APEs’ willingness to perform them) and official policy focusing APE efforts mainly on preventive services and health promotion. The demand for more curative services by community members is a result of having limited access to healthcare services other than those offered by APEs. CONCLUSION: This study highlights the need to pay attention to the determinants of demand and supply of community interventions in health, to understand the opportunities and challenges of the difficult interface role played by APEs and to create communication among stakeholders in order to build a stronger, more effective and equitable community programme.